4=(0.3f-4.5)

Simple and best practice solution for 4=(0.3f-4.5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4=(0.3f-4.5) equation:



4=(0.3f-4.5)
We move all terms to the left:
4-((0.3f-4.5))=0
We calculate terms in parentheses: -((0.3f-4.5)), so:
(0.3f-4.5)
We get rid of parentheses
0.3f-4.5
Back to the equation:
-(0.3f-4.5)
We get rid of parentheses
-0.3f+4.5+4=0
We add all the numbers together, and all the variables
-0.3f+8.5=0
We move all terms containing f to the left, all other terms to the right
-0.3f=-8.5
f=-8.5/-0.3
f=28+0.1/0.3

See similar equations:

| 10=2/5x-4 | | F=1/2(r+6.5 | | 1/2n-5+2/3×=7/6×+4 | | 82=-7x-4(2x+2) | | -6x+-5x+7+x=39 | | 6x-10-3x=11 | | 1.5(b+2)=2b-9+15b | | 4/3x+5=-11 | | 10-2x+11=13 | | X+x²=182 | | 7k+24=-16-3 | | x-4/4=8 | | 79=7-6x | | 20x^2+70x=0 | | 4|x–9|+6=-42 | | -2=7a+4-10a | | 2+1.1x-0.1x^2=3 | | 150x+3.50*255=2000 | | 5-4(n-5)=25+4 | | 5x+9=2(4x-3) | | 70=8r+6 | | 2(z-6)=6 | | 3/2-c-3c+4=5/2c+7-3 | | 4|x–9|+6=42 | | 16=-6x+2(2x+8) | | -5a+32=8a+19 | | 5x9=2(4x+3) | | 2=126/2=g | | -6=-30-8x | | -(3/5)x+(3/5)=(18/10) | | -10-3x=-64 | | 12-x=6-8(x) |

Equations solver categories